رسول اللہ صلی اللہ علیہ وسلم کے رخ انور کے تاثرات کی معنویت - Prof. Dr. Saeed Ul rehman (Seerat Studies, 2024)
The expression and features of the noble face of Prophet Muhammad (peace be upon him) hold deep spiritual and emotional significance. His face, described as radiant and full of light, was a reflection of his inner purity, compassion, and divine guidance. The impact of his facial expressions, from his smile to his serious demeanor, served as a profound means of communication, conveying love, mercy, wisdom, and leadership. Each of his expressions carried a deeper meaning, symbolizing his closeness to Allah, his role as a messenger, and his concern for humanity. His physical appearance, combined with his expressions, left a lasting impression on his companions, influencing their hearts and minds, and continues to inspire millions around the world. His face, in its entirety, embodied the perfect balance of humility, strength, and grace.